icacy test of hexane extract of Annona squamosa L seeds for Chrysomya bezziana larvae growth in vitro - Wardhana, April H; Widyastuti, E; Wiratmana, A.W.A; Muharsini, S; ., Darmono (Indonesian Journal of Animal and Veterinary Sciences, 2004)
Chrysomya bezziana is primer agent causing myiasis in livestock and human throughout Africa to Asia. At present, treatment of myiasis using chemical synthetic insecticide causing environment and livestock production contaminations. The aim of this study was to evaluate the effect of hexane extract of Annona squamosa L seed to kill C. bezziana as botanical insecticide. Three level and method preparation of larvae (L1, L2 and L3) were carried out. Meat blood mixture (MBM) and larval rearing media (LRM) were mixed with hexane extract of A. squamosa L seed and tested to 625 and 750 larvae (L1and L2 respectively), while for L3 625 larvae were soaked in the solution containing the hexane extract. This last preparation was carried out to observe the effect of toxic contact. Each larvae treatment was divided into 5 levels such as negative control using distillation water (PO), given 0.25% hexane extract (P I); 0.50% (P II); 0.75% (P III) and positive control was given with 0.10% AsuntolÂ®. This assay was to know digest toxic effect of hexane extract of A. squamosa L seed for those larvae. Number of 625 instar III larvae (L3) was soaked in the solution containing the hexane extract of A. squamosa L seed for 10 second, placed into vermicullite and incubated on 36oC. This assay was to know contact toxic effect of them. All of larvae were allowed to become pupae. Parameters oberserve were number of larvae death, pupae weight and number of pupae become into fly. The data was analyzed using Anova (5%) and Z test (5%) then smallest significant difference test (BNT 5%). The results showed that 0.50% of hexane extract of A. squamosa L seed was able to decrease pupae weight for L1 and L2 and to cause fail pupae become fly (P<0.05). Instar III larvae (L3) soaked in PI until P III and not effect to pupae weight, pupae become fly and survival of adult flies (P>0.05). Â  Key words: Chrysomya bezziana, myasis, srikaya, A. squamosa L, in vitro